The use of Charlson comorbidity index for observational studies using administrative data in Korea - Dong Wook Shin; Kyungdo Han (Precision and Future Medicine)
The number of large-scale epidemiological studies using administrative databases has rapidly increased in recent years. However, in observational studies, the outcomes of interest are heavily influenced by concurrent or pre-existing comorbidities, which act as confounders, and appropriate adjustment of comorbidities is essential to minimize bias. Although several comorbidity indices are available for this purpose, Charlson comorbidity index (CCI) is the most widely used one. The original version of the CCI was developed for use in longitudinal studies, to classify comorbidities that might alter the risk of mortality. It included 19 comorbidities, with each comorbidity having an assigned weight from 1 to 6; the total CCI score is a simple sum of the weights. Although the original CCI was based on a review of medical records, many modified versions have been proposed in subsequent studies using claims data. The CCI and its modified versions are used in virtually all clinical settings, including oncology, cardiology, respiratory care, emergency care, surgery, intensive care, and geriatrics. Appropriate use of a comorbidity index, such as the CCI, is necessary to minimize bias in observational studies in the era of increasing use of administrative data for healthcare research.